Social influence of the “rational flow” communication model of brand community participation in four-wheeled vehicle companies as a supporting correlation for knowledge exhibitions - Yodiansyah, Hefri; Kurniadi, Debby; Jummaulana, Hari (PT. Riset Press International, 2024)
This study aims to brand community research by proposing and testing a model of user participation in brand communities. The authors conceptualise three antecedents of brand community participation (e.g., individual, relationship, and group) based on qualitative results and an extensive literature review. The empirical analysis comes from data related to the official car brand community and supports most of the hypotheses. However, several differences emerge between users of official car brands and unofficial dealers regarding the correlation factor in the level of knowledge exhibition. Additionally, critical mass perceptions explain some of the social mechanisms underlying members' decisions to participate in brand communities. Finally, quantile regression analysis extends previous literature by showing that different exchange rules motivate brand users, depending on their level of participation. This paper discusses the managerial implications of these findings as well as some important issues and lines of research.